A New Non-touch Technique (Partha’s Technique) of Administering Spinal Anaesthesia in Paediatric Age Group- A Pilot Study - S Parthasarathy; Indubala Maurya (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Paediatric spinal anaesthesia is often the technique of choice in many short duration surgeries. However, the failure rate is higher with spinal anaesthesia in children than in adults. Aim: To evaluate if a non-touch technique of paediatric spinal anaesthesia can reduce anaesthetic failure. Materials and Methods: A pilot study was done in 10 paediatric patients from January 2018 to July 2018 in Mahatma Gandhi Medical College and Research Institute, Puducherry, India. Ten children posted for infra-umbilical surgeries in the age group of 4-10 years were given a sedative premedication with a combination of Pethidine and Midazolam They were kept in lateral position with the back much inside the edge of the table so that there was a considerable space between the table edge and the baby. Identification of the L3-L4 space was done by touching the patient. The 25-gauge quincke needle was pricked and the hub was held with the hand in the table without touching the patient. Results: The anaesthesia was successful with adequate level in all the patients; T8 in five patients and T10 in the other five patients. There were no significant side effects. Conclusion: From this pilot study on 10 patients, it can be suggested that the novel non-touch Partha’s technique is feasible and more successful with absent failure rate when administering spinal anaesthesia in the paediatric age group.